Hydrodynamic effects on flow accelerated corrosion at 120 °C and neutral pH conditions. (December 2018) - Madasamy, P.; Krishna Mohan, T.V.; Sylvanus, Andrews; Natarajan, E.; Rani, H.P.; Velmurugan, S.
Abstract: The objective of present study is to investigate the influence of bend geometry and the resulting flow phenomenon on the rate of metal loss due to Flow Accelerated Corrosion (FAC). Experiments were carried out with an aggressive chemistry of neutral pH (6.5–7.0) and at a temperature of 120 °C to minimize the time duration required to make unambiguous measurement of the change of wall thickness due to FAC. Measurement of FAC rate was carried out by installing a stainless steel FAC specimen holder, in which the bend pipe was assembled by stacking carbon steel rings to simulate a bend of 10 mm bore with 58 o bend angle and twice the bend diameter. The flow rate was adjusted to maintain a velocity of 7 m/s in the test section. The corrosion rate was experimentally quantified by the weight loss method, over an exposure period of two months at 120 °C in single phase of de-mineralized water. During this experiment, the value for the average thickness loss was found to be 0.9 mm. The turbulence patterns in the bend specimen holder were mapped by Computational Fluid Dynamics (CFD) parameters such as the wall shear stress and turbulent kinetic energy. The simulated mass transfer co-efficient and the corresponding corrosion rate correlated well with those of the measured values in various regions of the bend. The CFD studies showed that the intrados of the bend corrodes at a faster rate as compared to other regions of the bend. The change in temperature at a constant volumetric flow rate and in liquid phase does not significantly affect the velocity profile in the bend geometry. Highlights: Wall thickness reduction observed experimentally at 120 °C and neutral pH and the values computed by theory are in good agreement. Intrados of the bend is more prone to flow accelerated corrosion. The location of FAC attack in bend pipe does not depend on temperature; it depends on geometry only. Correlation exists between the experimental data obtained at 120 °C and CFD data at reactor operating temperature of 300 °C